THE INFLUENCE OF INHOMOGENEOUS PHANTOM ON ISODOSE CURVE USING MONTE CARLO SIMULATION - Riani Darmawan, Novi
Radiotherapy is a modality for treating cancer patients. Accurate dose calculation in radiotherapy can be obtained with Monte Carlo simulation. The purpose of this study is to determine the influence of field size variation on the beam characteristic, and determine the effect of field size and material variations on the isodose curve. The research was carried out using the PRIMO Varian Clinac 2100 of 6 MV photon mode with parameters following the standards of PRIMO. The field size used are 10x10 cm2 and 20x20 cm2 as well as the materials used in the phantom are water, water-bone-water, and water-lung-water. On beam characteristics obtained uncertainty 1.75% on profile width. The average angle increased to 2.14o and the average energy decreased to 1.46 MV. This can happen because increased field size lead to increased particle scattering. The width of isodose curve expand 100% and penumbra expand 50% on the isodose curve with field size variation. Moreover, the penumbra with bone addition narrows 25% and with lung addition expand 150%-300% on the material variation of the isodosis curve. However, the Penumbra with the bone addition expand 20% and with the lung addition narrowed 30% on the cutting isodose curve at z=10. The results obtained on the isodose curve due to differences in attenuation coefficients that affect particle absorption. This study concluded that field size affects the profile width, average angle, average energy, the width of the isodose curve and penumbra. Beside that, attenuation coefficient of the phantom material affects the width of penumbra on isodoses curve.